Optimizing Microclonal Propagation of Red Currant Cultivars: The Role of Nutrient Media, Sterilizers, and LED Lighting in Plant Adaptation - Olga Panfilova; Nelli Ryago; Gabrijel Ondrasek; Inna V. Knyazeva; Ibrahim Kahramanoğlu; Oksana Vershinina; Mikhail Tsoy; Andrey Yu Izmailov; Alexey S. Dorokhov (Horticulturae)
This study focuses on refining in vitro propagation protocols for red currant cultivars of the Ribes genus and evaluating the role of LED lighting in the adaptation of microplants. The cultivars ‘Red Lake’, ‘Englische Grosse Weisse’, ‘Marmeladnitsa’, and ‘Podarok Leta’ were successfully introduced into in vitro culture during their dormancy phase using 0.1% HgCl2 as a sterilizing agent. The period of spring introduction is not very efficient in connection with the intensive development of saprophytic microflora and weak morphogenesis microplants. Using 0.01% C9H9HgNaO2S sterilizer resulted in a decrease in the necrosis percentage, but an increase in mold proportion. The preparation of the plants with 12% H2O2 was considered environmentally not effective enough to obtain a large number of healthy microplants. The use of 12% H2O2 resulted in increased necrosis rates by 24.76% compared to 0.01% C9H9HgNaO2S and 0.1% HgCl2 sterilizers. The variety specificity of Ribesia plants in terms of the content of MS and LF nutrient media components was determined by the survival rate of explants, the formation of additional micro-shoots, and the morphological development. The MS medium with the addition of 1 mg∙L−1 BAP decreased the percentage of mold and necrosis infection and provided a high percentage of viable plants with optimal growth and reproduction rate. In contrast, the LF medium with the same concentration of 6-BAP resulted in poor explant quality and leaf chlorosis at later stages. The study also investigated the effects of different LED light spectra on morphological and physiological traits. For ‘Red Lake’ and ‘Englische Grosse Weisse’, RWUV-A (625–740 nm) lighting enhanced biomass and chlorophyll (Chl a and Chl a + b) accumulation, while the White (W) spectrum benefited ‘Podarok Leta’. Conversely, the RW spectrum with minimal green and no ultraviolet light restricted growth and photosynthetic pigment accumulation across all cultivars, promoting compact plant structures. The RWUV-A lighting condition resulted in the highest NDVI values across all cultivars, indicating an improved physiological status and biomass accumulation. These findings underscore the importance of refining the microclonal reproduction protocols for Ribesia subgenus representatives, emphasizing the genotype-specific light modulation during the proliferation stage. The study highlights the utility of the MS medium and tailored light conditions in enhancing the effectiveness of propagation techniques for producing high-quality planting material.